Technique selection in young female gymnasts: Elbow and wrist joint loading during the cartwheel and round-off - Farana, R.; Exell, T.; Strutzenberger, G.; Irwin, G. (European Journal of Sport Science, 2018)
Biophysical loading of the elbow and wrist is a potential reason for chronic lesions in gymnastics and present a real concern for coaches, scientist and clinicians. Previous research has identified injury risk factors during round-off (RO) skills in elite female gymnasts. The aim of this study was to investigate key elbow and wrist joint injury risk factors during different techniques of fundamental cartwheel (CW) and RO skills performed by young female artistic gymnasts. Seventeen active young female gymnasts performed 30 successful trials of both CW and RO from a hurdle step with three different hand positions (parallel (10), T-shape (10) and reverse (10)). Synchronised kinematic (240 Hz) and kinetic (1200 Hz) data were collected for each trial. One-way repeated measures ANOVA and effect size (ES) were used for statistical analysis. The results showed statistically significant differences (P < .05) and large ES (>0.8) among hand positions for peak vertical ground reaction force (VGRF), peak elbow compression force, peak wrist compression force, elbow internal adduction moment and wrist dorsiflexion angle. In conclusion, the parallel and reverse techniques increase peak VGRF, elbow and wrist compression forces, and elbow internal adduction moment. These differences indicate that the parallel and reverse techniques may increase the potential of elbow and wrist injuries in young gymnasts compared with the T-shape technique; this is of particular importance with the high frequency of the performance of these fundamental skills.